Subsequent treatment(s) for prostate cancer recurrence following radical prostatectomy deteriorate functional outcome and quality of life - de Reijke, Theo M. (Translational Cancer Research, 2017)
Radical prostatectomy is indicated in patients with intermediate- and high-risk prostate cancer. Especially, in these patients there is the risk on positive surgical margins and positive lymph nodes. In case positive surgical margins are found in the pathological specimen it is questioned still if immediate adjuvant radiotherapy should be offered to the patient (1-3). There are three trials underway evaluating the optimal timing of radiotherapy following radical prostatectomy in case of pT3 disease or positive surgical margins (RADICALS, RAVES and GETUG-17) (4). It is obvious that patients receiving subsequent treatments will experience more side effects. The rate of side effects was evaluated in his adjuvant radiotherapy trials, but in these trials no validated questionnaires were used. Adam et al. did use validated questionnaires in their study (5).